BOUGUER ANOMALY AND SEDIMENT THICKNESS ESTIMATION AT THE TEHORU GEOTHERMAL AREA - Salman Hamja Siombone; Mursaid Dahlan (JGE (Jurnal Geofisika Eksplorasi), 2026)
Tehoru Village, Tehoru District, Central Maluku Regency, has significant geothermal potential. This study aims to examine Bouguer anomalies, reduced-Bouguer density, sediment thickness estimation, and shallow structures using TOPEX gravity data and SRTM DEM in an area of ±191.70 km². The processing results show Complete Bouguer Anomaly (CBA) values ranging from 6.80 to 73.60 mGal, with Bouguer densities of 1.77 to 1.79 g/cm³, indicating the dominance of alluvial sediments. Anomaly separation using the Moving Average method yields residual anomalies ranging from -4.60 to 47.70 mGal, with low anomalies dominant in the southwest of the geothermal manifestation. Spectral analysis shows an average sediment thickness of ±246.07 m. In contrast, SVD analysis, lineament maps, and rose diagrams indicate that geothermal manifestations develop in tight fault-related zones with a dominant northeast–southwest orientation. Although effective for regional analysis, TOPEX gravity data interpretation has limitations for imaging shallow structures and sediment thickness variations, as small anomalies are often obscured by its relatively low spatial resolution. Overall, the Tehoru geothermal system is controlled by several local fault-related zones and significant sediment thickness, which influence its response to tectonic activity.